PENGGUNAAN MEDIAN PADA PERLINTASAN SEBIDANG UNTUK MENGURANGI PELANGGARAN PINDAH LAJUR (STUDI KASUS DI PERLINTASAN JALAN A.R. HAKIM KOTA TEGAL) - Kurniawan, Hanung; Prasetianto, Eko; Nurhakim, Rifki (FSTPT Indonesia, 2015)
The number of accidents in railway crossings lately, is of particular concern for us to examine the phenomenon that the caused the accident, then we do research at railway crossings in the city of Tegal. Survey Methods used in this study is the direct observation. while Average Daily Traffic data (ADT) is used Secondary data, from the 2013 survey PKTJ Midshipman. In this study using the method of analysis